Sport psychology : concepts and applications - Cox, Richard H., 1941- (New York : McGraw-Hill, 2012)
'Sport Psychology: Concepts and Applications shows how concepts supported by current scientific research can be used to address issues and situations encountered everyday by physical activity specialists, coaches, athletic trainers, and athletes. This introduction to sport and exercise psychology addresses practical issues, such as dealing with anxiety, arousal, and stress; developing coping, relaxation, motivation, and energizing strategies; understanding the effects of an audience on human performance; building team cohesion; and preventing burnout and other negative effects'--
'In recent years, interest in applied sport and exercise psychology has soared. Sport Psychology:Concepts and Applications is written for students who are interested in learning about sport and exercise psychology as an academic discipline and in using that knowledge in applied settings. The book is designed primarily for upper-level undergraduate students, but instructors can easily adapt the book as a foundation text for graduate students by supplementing the text with current articles from sport psychology journals'--
Includes bibliographical references (p. 492-539) and indexes.
Keywords: Sports -- Psychological aspects; Coaching (Athletics) -- Psychological aspects; Athletes -- Psychology